ROLE OF INTERNET IN INSURANCE SERVICES REALIZATION - N. Prikazyuk (Vìsnik. Kiïvsʹkogo Nacìonalʹnogo Unìversitetu ìmenì Tarasa Ševčenka. Ekonomìka, 2014)
The role of the Internet in the implementation of insurance products is investigated. It is founded the Internet in insurance performs presentable and realizable function. The benefits of using Internet technologies for business of insurance market are determined.